PENGARUH KEPUTUSAN KEUANGAN, PROFITABILITAS, DAN KEPEMILIKAN MANAJERIAL TERHADAP NILAI PERUSAHAAN PADA SEKTOR KEUANGAN - AFRILIYA DISTYOWATI, AYU; PURWOHANDOKO, (Jurnal Ilmu Manajemen (JIM), 2019)
The purpose of this research is to determine the effect of three financial decisions (dividend policy, financing decision, investment decision), profitability, and managerial ownership toward firm value in the financial sector listings in Indonesia Stock Exchange (IDX) period 2013-2017. This study uses quantitative research type, with secondary data in the form of company financial statements obtained from the official website of the Indonesia Stock Exchange (IDX). The sample used are 19 companies with purposive sampling method. The analysis technique used is multiple linear regression analysis with the help of SPSS 18 software analysis tools. The results of research showed that dividend policy have no effect to firm value, while financial decision, investment decision, profitability have an positive effect on firm value, and managerial ownership have an negative effect on firm value. Keywords: financial decision; firm value; managerial ownership; profitability.